Volatility spillovers among developed and developing countries: The global foreign exchange markets - Walid Abass Mohammed (Journal of Risk and Financial Management, 2021)
In this paper, we investigate the "static and dynamic" return and volatility spillovers' transmission across developed and developing countries. Quoted against the US dollar, we study twenty-three global currencies over the time period 2005-2016. Focusing on the spillover index methodology, the generalised VAR framework is employed. Our findings indicate no evidence of bi-directional return and volatility spillovers between developed and developing countries. However, unidirectional volatility spillovers from developed to developing countries are highlighted. Furthermore, our findings document significant bi-directional volatility spillovers within the European region (Eurozone and non-Eurozone currencies) with the British pound sterling (GBP) and the Euro (EUR) as the most significant transmitters of volatility. The findings reiterate the prominence of volatility spillovers to financial regulators.
Keywords: G01; G1; F3; 330; financial crisis; financial interdependence; foreign exchange market; return spillover; VAR framework; variance decomposition; volatility spillover